Psoriasis and autoimmunity - Sticherling, Michael (Autoimmunity Reviews, 2016)
Psoriasis is one of the most common chronic inflammatory human skin diseases. Though clinically well characterized, the exact etiological and pathogenic mechanisms are still not known in detail. Current knowledge indicates distinct overlap to other inflammatory as well as autoimmune disorders. However, the one or more relevant autoantigens could not be characterized so-far. On the other side, several autoimmune diseases were shown to be associated with psoriasis. In addition, serological autoimmune phenomena, namely diverse circulating specific autoantibodies could be demonstrated in the past. A matter of current debate is if psoriasis is a primary autoimmune disease or secondarily evolving into autoimmunity as seen in other chronic inflammatory diseases. Related to this aspect is the concept of autoinflammation versus autoimmunity where psoriasis shares mechanisms of both entities. Though T-cells remain among the most important cellular players in the pathogenesis of psoriasis and current therapeutic strategies successfully target these cells or their products irrespective of these concepts, autoimmunity if relevant will add to the treatment armamentarium by using protective and prophylactic antigen-specific modalities.
EVALuna2:19626